The Dynamics of Islamic Civilization: The Process of the Formation of the Abbasid Dynasty - Harlina, Lily (International Journal of Islamic Studies, 2025)
This article discusses the history of the Abbasid dynasty, as we all know that the formation of the Abbasid dynasty is inseparable from the long history and influence of the fall of the Umayyad dynasty. This writing is a tangible symbol that the long history of the Abbasid dynasty will be documented in a journal entitled "The Dynamics of Islamic Civilization: The Process of the Formation of the Abbasid Dynasty." Like the common discussions that the Umayyad dynasty was the Islamic rulers who created a monarchy system (a government system in the form of a kingdom). Previously, the system used was democratic, and therefore, this kingdom gained its power through diplomacy, violence, and deception, allowing the dynasty to grow rapidly. Unlike previous leadership, during the era of the Khalifaur rasyidin, the society chose their leaders using a democratic system. This system has been in place since the time of Prophet Muhammad SAW. At that time, the existence of the Umayyad dynasty lasted for 90 years (680-750 AD).